Reflective adhesive tape without backing paper and preparation method of reflective adhesive tape

By adopting a multi-layer structure reflective tape design and setting a photochromic layer in it, the problem of unstable performance of existing reflective tape in different lighting environments is solved, and adaptive optical performance adjustment under variable lighting conditions is achieved, and visibility and visual comfort are improved.

CN119875524AInactive Publication Date: 2025-04-25WENZHOU YINGKAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411987771.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing reflective tape is unstable under different lighting environments and cannot adaptively adjust the reflective or light transmission performance, resulting in insufficient effectiveness in dynamic environments.

Method used

A multi-layer structure reflective tape design is adopted, including foam layer, reflective layer, light transmitting layer group, mesh layer, adhesive layer and centrifugal silicone oil layer. A photochromic layer is set in the multi-layer film structure. The transmission and reflection characteristics of light are automatically adjusted by reacting with metal ions through ultraviolet photochromic dyes.

Benefits of technology

It realizes automatic adjustment of light transmission and reflection characteristics under different lighting environments, improves visibility and visual comfort under variable lighting conditions, and meets the needs of different lighting environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875524A_ABST
    Figure CN119875524A_ABST
Patent Text Reader

Abstract

The invention discloses a reflective adhesive tape without backing paper and a preparation method thereof, the reflective adhesive tape is formed by combining a foam layer, a reflective layer, a light-transmitting layer group, a net layer, an adhesive layer and a centrifugal silicone oil layer, and the unique function of each layer of material is fully exerted through the multi-layer structural design. The foam layer provides better buffering and adhesive force, the light reflecting layer ensures efficient light reflection, the light transmitting layer can effectively improve the light transmitting effect through layers with different refractive indexes, and the design of the net layer and the adhesive layer ensures stable connection between the light reflecting layer and the foam layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of reflective adhesive tapes, and in particular relates to a reflective adhesive tape without a backing paper and a preparation method thereof. Background Art

[0002] Reflective tapes are widely used in traffic signs, road construction, vehicle decoration, emergency signs and other fields, mainly used to improve visibility at night or in low-visibility environments. Existing reflective tapes are usually composed of a single reflective material, which has certain advantages in light reflection, but has large performance differences in strong light and low light environments, and lacks durability and adaptability.

[0003] Traditional reflective tapes are usually based on polyester film and combined with materials such as tiny glass beads or reflective film to enhance the ability to reflect light and thus improve visibility. These reflective materials achieve their functions by reflecting light, especially under strong light or vehicle lights, and can effectively reflect light to improve the visibility of signs or warnings. However, although this traditional design has a high reflectivity in specific environments, especially under strong light conditions, it has some obvious limitations.

[0004] First, the reflective effect of traditional reflective tapes mainly depends on the light reflective properties of glass beads or reflective films, and the performance of these materials cannot be flexibly adjusted under different lighting conditions. For example, in weak or low light conditions, the reflective ability of reflective tapes decreases significantly, and in strong light conditions, the reflective effect may reach saturation and cannot be further improved. In addition, these reflective materials usually do not have the ability to effectively interact with changes in ambient lighting, and therefore cannot adapt to changes in different ambient lighting conditions such as day and night, sunny and cloudy days, etc.

[0005] Secondly, traditional reflective tape generally lacks photochromic properties, that is, it cannot adjust its own reflection or light transmission properties according to changes in light intensity. This means that although reflective tape performs well under strong light, when the ambient light changes (such as from strong light during the day to low light at night or weak light on a cloudy day), its performance cannot be adaptively adjusted, thus affecting its effectiveness in different lighting environments. The lack of photochromic properties makes the performance of traditional reflective tape in dynamic environments insufficient to meet the changing needs of use.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a reflective adhesive tape without a backing paper and a preparation method thereof, and solve the problems raised in the above-mentioned background technology.

[0008] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0009] A reflective adhesive tape without a backing paper comprises: a film cylinder, the outer surface of which is wound with a reflective adhesive tape, the reflective adhesive tape being composed of a foam layer, a reflective layer, a light-transmitting layer group, a mesh layer, an adhesive layer, and a centrifugal silicone oil layer, the reflective layer being bonded to the top of the foam layer, the mesh layer being bonded between the reflective layer and the foam layer, and a combination groove adapted to the mesh layer being provided between the reflective layer and the foam layer, the light-transmitting layer being bonded to the surface of the reflective layer, the adhesive layer being bonded to the bottom of the foam layer, and a release silicone oil layer being applied to the bottom of the adhesive layer.

[0010] Optionally, the light-transmitting layer group includes at least one light-transmitting layer, and the light-transmitting layer is one of a transparent PET film layer, a silica sol film, an aluminum oxide sol film, and a titanium oxide sol film.

[0011] Optionally, the light-transmitting layer group is sequentially arranged from top to bottom as a silica sol film, an alumina sol film, and a titanium oxide sol film, wherein the refractive index of the silica sol film is 1.55, the refractive index of the alumina sol film is 1.6, and the refractive index of the titanium oxide sol is 1.65.

[0012] Optionally, the steps for preparing a light-transmitting layer group with multiple refraction angles are:

[0013] TEOS was mixed with ethanol, and deionized water was added for hydrolysis reaction. The catalyst was hydrochloric acid. After stirring evenly, the mixture was allowed to stand for 2 hours to form a transparent sol. Then, the sol was evenly coated on the substrate surface by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Then, the coated substrate was placed at 60°C for 30 minutes to dry, and then heat treated at 300°C for 1 hour to convert it into a SiO2 film.

[0014] Aluminum chloride and ethanol were dissolved, deionized water was added for hydrolysis reaction, and stirred for 2 hours to obtain a uniform alumina sol. Then, the alumina sol was coated on the silica sol film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was placed at 300°C for 1 hour for heat treatment to convert it into an alumina film.

[0015] Tetraisopropyl titanate was dissolved in ethanol, deionized water was added for hydrolysis reaction, and the mixture was stirred for 2 hours to obtain titanium oxide sol. Then, the titanium oxide sol was coated on the aluminum oxide film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was heat treated at 350°C for 1 hour to form a titanium oxide film with a high refractive index.

[0016] Optionally, a photochromic layer is provided between every two adjacent films in the multilayer film structure, and the preparation method thereof comprises the following steps:

[0017] Dissolving silver nitrate in ethanol to obtain a solution containing metal ions, then mixing the ultraviolet photochromic dye with the metal ion solution and stirring them evenly to obtain a mixed solution;

[0018] The film is evenly sprayed on the surface of the substrate by spraying, and then the sprayed film is exposed to an ultraviolet light source for curing, so that the ultraviolet photochromic dye reacts and combines with the metal ions, and the curing time is 10-20 minutes;

[0019] After curing, the film was heat treated at 120° C. for 30 minutes.

[0020] Optionally, the mass ratio of silver nitrate to ethanol is 1:50 g, and the mass ratio of the ultraviolet photochromic dye to silver nitrate is 1:0.2.

[0021] Optionally, the mass ratio of TEOS to ethanol in the silica sol film is 1:10, the ratio of water to silicon source is (2-4):1, the ratio of aluminum chloride to ethanol in the alumina sol film is 1:10, the ratio of water to silicon source is (2-4):1, the ratio of tetraisopropyl titanate to ethanol in the titanium oxide sol film is 1:10, the ratio of water to silicon source is (2-4):1

[0022] Optionally, the adhesive layer is one of a pressure-sensitive adhesive and a composite adhesive, and the thickness of the adhesive layer is 85-100 μm.

[0023] A method for preparing the reflective adhesive tape without liner, characterized in that a foam layer, a reflective layer, a light-transmitting layer group, a mesh layer, an adhesive layer and a centrifugal silicone oil layer are sequentially bonded using a thermal adhesive.

[0024] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0025] 1. The reflective tape is composed of a foam layer, a reflective layer, a light-transmitting layer group, a mesh layer, an adhesive layer and a centrifugal silicone oil layer. This multi-layer structure design gives full play to the unique functions of each layer of material. The foam layer provides better cushioning and adhesion, the reflective layer ensures efficient light reflection, and the light-transmitting layer can effectively improve the light transmission effect through the layers of different refractive indices. The design of the mesh layer and the adhesive layer ensures a stable connection between the reflective layer and the foam layer.

[0026] 2. By setting up a photochromic layer, the reflective tape can automatically adjust the light transmission and reflection characteristics according to changes in ambient lighting conditions. Under ultraviolet light, the photochromic dye can react and combine with metal ions to show adjustable transmittance and reflectivity to meet the needs of different lighting environments.

[0027] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0029] In the figure:

[0030] Figure 1 It is a schematic diagram of the three-dimensional structure of the tape structure;

[0031] Figure 2 It is a schematic diagram of the cross-sectional structure of the tape structure;

[0032] Figure 3 Schematic diagram of the honeycomb structure of the foam layer;

[0033] Figure 4 A schematic diagram of the network layer structure.

[0034] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0035] 1. Film roll; 2. Foam layer; 3. Reflective layer; 4. Translucent layer; 5. Mesh layer; 6. Adhesive layer; 7. Centrifugal silicone oil layer.

[0036] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0037] The present invention will now be described in further detail with reference to the accompanying drawings.

[0038] See also Figure 1-4As shown, in this embodiment, a reflective adhesive tape without a backing paper is provided, including a film roll 1, the outer surface of the film roll 1 is wrapped with a reflective tape, and the reflective tape is composed of a foam layer 2, a reflective layer 3, a light-transmitting layer 4 group, a mesh layer 5, an adhesive layer 6, and a centrifugal silicone oil layer 7. The reflective layer 3 is bonded to the top of the foam layer 2, the mesh layer 5 is bonded between the reflective layer 3 and the foam layer 2, and a combination groove adapted to the mesh layer 5 is provided between the reflective layer 3 and the foam layer 2, the light-transmitting layer 4 is bonded to the surface of the reflective layer 3, the adhesive layer 6 is bonded to the bottom of the foam layer 2, and the release silicone oil layer is applied to the bottom of the adhesive layer 6. When the reflective layer 3 is bonded to the foam layer 2, the mesh layer 5, and the light-transmitting layer 4, pressure-sensitive adhesive is used. The shape of the holes in the mesh layer 5 is one of prism, rectangle, polygon, and circle, a honeycomb structure is provided below the foam layer 2, and the adhesive layer 6 is located inside the honeycomb.

[0039] In this embodiment, the light-transmitting layer 4 group includes at least one light-transmitting layer 4, and the light-transmitting layer 4 is one of a transparent PET film layer, a silica sol film, an aluminum oxide sol film, and a titanium oxide sol film.

[0040] In this embodiment, the adhesive layer 6 is one of a pressure-sensitive adhesive and a composite adhesive, and the thickness of the adhesive layer 6 is 85-100 μm.

[0041] Embodiment 1:

[0042] In this embodiment, the four groups of light-transmitting layers are arranged from top to bottom in order: a silica sol film, an alumina sol film, and a titanium oxide sol film, wherein the refractive index of the silica sol film is 1.55, the refractive index of the alumina sol film is 1.6, and the refractive index of the titanium oxide sol is 1.65.

[0043] In this embodiment, the steps for preparing four groups of light-transmitting layers with multiple refraction angles are as follows:

[0044] TEOS was mixed with ethanol, and deionized water was added for hydrolysis reaction. The catalyst was hydrochloric acid. After stirring evenly, the mixture was allowed to stand for 2 hours to form a transparent sol. Then, the sol was evenly coated on the substrate surface by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Then, the coated substrate was placed at 60°C for 30 minutes to dry, and then heat treated at 300°C for 1 hour to convert it into a SiO2 film.

[0045] Aluminum chloride and ethanol were dissolved, deionized water was added for hydrolysis reaction, and stirred for 2 hours to obtain a uniform alumina sol. Then, the alumina sol was coated on the silica sol film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was placed at 300°C for 1 hour for heat treatment to convert it into an alumina film.

[0046] Tetraisopropyl titanate was dissolved in ethanol, deionized water was added for hydrolysis reaction, and the mixture was stirred for 2 hours to obtain titanium oxide sol. Then, the titanium oxide sol was coated on the aluminum oxide film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was heat treated at 350°C for 1 hour to form a titanium oxide film with a high refractive index.

[0047] In a multilayer film structure, a photochromic layer is provided between every two adjacent films, and the preparation method thereof comprises the following steps:

[0048] Dissolving silver nitrate in ethanol to obtain a solution containing metal ions, then mixing the ultraviolet photochromic dye with the metal ion solution and stirring them evenly to obtain a mixed solution;

[0049] The film is evenly sprayed on the surface of the substrate by spraying, and then the sprayed film is exposed to an ultraviolet light source for curing, so that the ultraviolet photochromic dye reacts and combines with the metal ions, and the curing time is 20 minutes;

[0050] After curing, the film was heat treated at 120° C. for 30 minutes.

[0051] In this embodiment, the mass ratio of silver nitrate to ethanol is 1:50 g, and the mass ratio of the ultraviolet photochromic dye to silver nitrate is 1:0.2.

[0052] In this embodiment, the mass ratio of TEOS to ethanol in the silica sol film is 1:10, the ratio of water to silicon source is 2:1, the ratio of aluminum chloride to ethanol in the alumina sol film is 1:10, the ratio of water to silicon source is 2:1, and the ratio of tetraisopropyl titanate to ethanol in the titanium oxide sol film is 1:10, and the ratio of water to silicon source is 2:1. Photochromic materials can automatically adjust their light transmittance and reflectivity according to changes in light intensity. For example, under strong light, the reflective properties of the material are enhanced, thereby reducing light penetration and heat absorption; while in weak light or at night, the material maintains a high light transmittance, thereby improving visibility and visual comfort.

[0053] In addition, in the fields of reflective tapes, road markings, and automotive reflective coatings, photochromic materials can enhance the reflective effect under strong light and maintain light transmittance in low light or at night. This property makes photochromic materials particularly suitable for smart reflective materials and adaptive optical surfaces, which can improve traffic safety, building visibility, and nighttime lighting effects.

[0054] Comparative Example 1: The reflective layer uses only one transparent PET film layer to adopt a composite structure.

[0055] Comparative Example 2: The reflective layer uses only one of the silica sol film, the alumina sol film, and the titanium oxide sol film;

[0056] Comparative Example 3: A composite structure in which the reflective layer is formed by only aluminum oxide sol film and titanium oxide sol film;

[0057] Comparative Example 4: A composite structure in which the reflective layer is formed only of silica sol film and alumina sol film.

[0058] Test Example 1: Reflectivity Test

[0059] The reflectivity test is conducted using a standard optical reflectivity measuring instrument (such as a spectroscopic reflectometer). The test conditions include strong light (UV light, 400W), weak light (LED light source, 100W) and night environment (no light source).

[0060]

[0061] * It showed excellent performance under strong light irradiation, with a reflectivity of up to 92%. This performance is not only much better than other comparative samples, but also shows that the multilayer structure of the composite film effectively enhances the reflection and scattering effects of light, especially under high-intensity ultraviolet light or sunlight irradiation, which can significantly improve the reflective effect. This is because the design of the composite film utilizes the different refractive indices of silica sol, aluminum oxide and titanium oxide, so that the light is refracted and reflected multiple times in each layer of the film, thereby optimizing the propagation path and reflection intensity of the light and achieving the best reflection effect. Its reflective performance is particularly outstanding under high light intensity conditions, and can effectively improve the reflectivity of visible light, so that its use effect under strong sunlight is better than that of traditional single materials. Test Example 2: Photochromic response speed test. In contrast, the reflectivity of Comparative Example 1 is relatively low, only about 80%, and performs poorly under strong light irradiation. This shows that the single-layer PET film cannot effectively enhance the reflection effect, and its reflectivity is significantly lower than that of the composite film structure under strong light conditions. This is because the PET film only provides a single optical interface, and without multi-layer refractive index regulation, light can easily penetrate and fail to be effectively reflected back. Therefore, although the transparent PET film has a certain reflective effect under weak light conditions and is suitable for use in low-intensity light environments, its reflective performance under strong light and weak light environments is obviously insufficient and cannot be compared with the composite film structure of Example 1.

[0062] Test the response time of UV photochromic dye under UV light source. The wavelength of UV light source is 365nm, and the reaction time is from the time when the dye starts to develop color to the time when it reaches the maximum reflectivity.

[0063]

[0064]

[0065] In Example 1, the response time of the photochromic performance is excellent, about 12 seconds, which shows that the composite film structure can respond quickly to external lighting conditions. Especially under ultraviolet light irradiation, the interaction between the photochromic dye and the metal ions causes the reflective properties of the film to change rapidly, thereby achieving dynamic adjustment of reflectivity and transmittance. This rapid response enables the composite film of Example 1 to adjust its reflective and light transmittance properties in real time under different lighting environments, improve reflectivity under strong light irradiation, and enhance light transmittance under low light or at night, thereby providing excellent visual effects and optical properties in a variety of environments.

[0066] In contrast, the photochromic performance of Comparative Examples 2, 3 and 4 failed to show significant effects. In these comparative samples, although some films use similar photochromic dyes, the lack of appropriate interaction between metal ions and dyes, or the interlayer structure is not optimized, resulting in a small change in reflectivity and transmittance. The response speed of these comparative samples is slow, usually requiring tens of seconds or even longer to change, and the change range is limited. This shows that the photochromic performance of these samples is not sufficient to adapt to the rapid changes in ambient light intensity, the reflectivity and transmittance are not significantly enhanced under ultraviolet light, and the performance under other lighting conditions is also relatively stable, lacking the necessary dynamic adjustment capabilities.

[0067] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A reflective adhesive tape without liner, characterized in that: include: A reflective adhesive tape without a backing paper, characterized by comprising: A film drum 1, the outer surface of which is wrapped with a reflective tape, the reflective tape being composed of a foam layer 2, a reflective layer 3, a light-transmitting layer 4 group, a mesh layer 5, an adhesive layer 6, and a centrifugal silicone oil layer 7. The reflective layer 3 is bonded to the top of the foam layer 2, the mesh layer 5 is bonded between the reflective layer 3 and the foam layer 2, and a combination groove adapted to the mesh layer 5 is provided between the reflective layer 3 and the foam layer 2, the light-transmitting layer 4 is bonded to the surface of the reflective layer 3, the adhesive layer 6 is bonded to the bottom of the foam layer 2, and a release silicone oil layer is applied to the bottom of the adhesive layer 6.

2. The reflective adhesive tape without liner according to claim 1, characterized in that: The light-transmitting layer 4 group includes at least one light-transmitting layer 4, and the light-transmitting layer 4 is one of a transparent PET film layer, a silica sol film, an aluminum oxide sol film, and a titanium oxide sol film.

3. The reflective adhesive tape without liner according to claim 1, characterized in that: The four groups of light-transmitting layers are arranged from top to bottom in order: a silica sol film, an alumina sol film, and a titanium oxide sol film, wherein the refractive index of the silica sol film is 1.55, the refractive index of the alumina sol film is 1.6, and the refractive index of the titanium oxide sol is 1.

65.

4. The reflective adhesive tape without liner according to claim 1, characterized in that: The steps for preparing four groups of light-transmitting layers with multiple refraction angles are as follows: TEOS was mixed with ethanol, and deionized water was added for hydrolysis reaction. The catalyst was hydrochloric acid. After stirring evenly, the mixture was allowed to stand for 2 hours to form a transparent sol. Then, the sol was evenly coated on the substrate surface by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Then, the coated substrate was placed at 60°C for 30 minutes to dry, and then heat treated at 300°C for 1 hour to convert it into a SiO2 film. Aluminum chloride and ethanol were dissolved, deionized water was added for hydrolysis reaction, and stirred for 2 hours to obtain a uniform alumina sol. Then, the alumina sol was coated on the silica sol film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was placed at 300°C for 1 hour for heat treatment to convert it into an alumina film. Tetraisopropyl titanate was dissolved in ethanol, deionized water was added for hydrolysis reaction, and the mixture was stirred for 2 hours to obtain titanium oxide sol. Then, the titanium oxide sol was coated on the aluminum oxide film by spin coating. The spin coating speed was set to 2500 rpm and the coating time was 30 seconds. Finally, after drying, the substrate was heat treated at 350°C for 1 hour to form a titanium oxide film with a high refractive index.

5. The reflective adhesive tape without liner according to claim 1, characterized in that: In a multilayer film structure, a photochromic layer is provided between every two adjacent films, and the preparation method thereof comprises the following steps: Dissolving silver nitrate in ethanol to obtain a solution containing metal ions, then mixing the ultraviolet photochromic dye with the metal ion solution and stirring them evenly to obtain a mixed solution; The film is evenly sprayed on the surface of the substrate by spraying, and then the sprayed film is exposed to an ultraviolet light source for curing, so that the ultraviolet photochromic dye reacts and combines with the metal ions, and the curing time is 10-20 minutes; After curing, the film was heat treated at 120° C. for 30 minutes.

6. The reflective adhesive tape without liner according to claim 1, characterized in that: The mass ratio of silver nitrate to ethanol is 1:50 g, and the mass ratio of ultraviolet photochromic dye to silver nitrate is 1:0.

2.

7. The reflective adhesive tape without liner according to claim 1, characterized in that: The mass ratio of TEOS and ethanol in the silica sol film is 1:10, and the ratio of water to silicon source is (2-4):

1. The ratio of aluminum chloride and ethanol in the alumina sol film is 1:10, and the ratio of water to silicon source is (2-4):

1. The ratio of tetraisopropyl titanate and ethanol in the titanium oxide sol film is 1:10, and the ratio of water to silicon source is (2-4):

1.

8. The reflective adhesive tape without liner according to claim 1, characterized in that: The adhesive layer 6 is one of a pressure-sensitive adhesive and a composite adhesive, and the thickness of the adhesive layer 6 is 85-100 μm.

9. A method for preparing the linerless reflective adhesive tape according to claims 1 to 8, characterized in that: Use thermal adhesive to sequentially bond the foam layer, the reflective layer, the light-transmitting layer group, the mesh layer, the adhesive layer, and the centrifugal silicone oil layer.